Greenhouse gas reduction through the introduction of electric vehicles in urban zones - Mello, Igoor Morro [UNESP] (2020)
The decarbonizing the transportation system through the introduction of electric vehicles in urban zones has intensified in recent years. This paper presents a methodology for modeling electric vehicles in an urban zone using transportation tools to determine the decrease in greenhouse gas emission values in the main avenues and streets due to various electric mobility technologies and the analysis of charging stations in the electric network. The results of the proposed methodology are the spatial databases that can be observed in geographic information systems to assist city planners in the incentive policies for decarbonization, distribution planners in the location of the infrastructure for charging and the measurement of the impacts on voltage levels with the electric vehicle recharge at charging stations to provide information to distribution network planners.